Evolution of endonuclease IV protein family: an in silico analysis - Kanchan, Swarna (3 Biotech, 2019)
DNA repair is one of the key cellular events which balances between evolvability and integrity of the genome. Endonuclease IV enzymes are class II AP endonucleases under base excision repair pathway which act on abasic site and break the phosphodiester bond at the 5′ side. The role and activity of endonuclease IV proteins vary among different organisms; even it is absent in higher eukaryotes. The evolution of this protein family was studied by analyzing all homologs of the endonuclease IV protein family through different in silico techniques including phylogenetic tree generation and model building. The sequence analysis revealed four consensus sequence motifs within the AP2EC domain which are functionally important and conserved throughout the evolution process. It was also observed that the species and endonuclease IV gene evolution shape up differently in most of the organisms. Presence of the mitochondria-targeted signal peptides in fungal species Saccharomyces and Coccidioides suggest a possible endosymbiotic transfer of endonuclease IV genes to lower eukaryotes. Evolutionary changes among various clades in the protein-based phylogenetic tree have been investigated by comparison of homology models which suggests the conservation of overall fold of endonuclease IV proteins except for few alterations in loop orientation in few clades. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13205-019-1696-6) contains supplementary material, which is available to authorized users.